A monographic revision of Retrophyllum (Podocarpaceae). (1st June 2017) - Mill, Robert R.
Abstract : In the revision of Retrophyllum published in a previous issue of the Edinburgh Journal of Botany, the barcode for the specimen designated on page 208 line 10 as lectotype of Retrophyllum minus (Carrière) C.N. Page was incorrectly given as P00118110 instead of P00188110.